Electromagnetic Control by Actuating Kirigami-Inspired Shape Memory Alloy: Thermally Reconfigurable Antenna application - Minjae Lee; Sukwon Lee; Sungjoon Lim (Sensors, 2021)
Electromagnetic responses are generally controlled electrically or optically. However, although electrical and optical control allows fast response, they suffer from switching or tuning range limitations. This paper controls electromagnetic response by mechanical transformation. We introduce a novel kirigami-inspired structure for mechanical transformation with less strength, integrating a shape memory alloy actuator into the kirigami-inspired for mechanical transformation and hence electromagnetic control. The proposed approach was implemented for a reconfigurable antenna designed based on structural and electromagnetic analyses. The mechanical transformation was analyzed with thermal stimulus to predict the antenna geometry and electromagnetic analysis with different geometries predicted antenna performance. We numerically and experimentally verified that resonance response was thermally controlled using the kirigami-inspired antenna integrated with a shape memory alloy actuator.